Legal particularities of AI technology usage in real-world data formation - V. S. Malichenko; A. O. Gadzhieva; N. I. Platonova; A. Yu. Solovieva-Oposhnyanskaya (Фармакоэкономика, 2024)
In recent decades, technological progress has contributed to a consistent change in approaches to organizing the provision of medical care in various regions of the world. Electronic data-gathering systems make it possible to create extensive information databases about the health status of the population of certain territories or entire states. The introduction of technological solutions based on the use of artificial intelligence (AI) technologies makes it possible to provide a systematic analysis of large volumes of information, as well as to develop new treatment methods of life-threatening diseases. The use of AI technologies not only has significant potential for improving the organization of medical care, but also brings essential risks of human rights restriction, it may also form discriminatory practices or even cause harm to health. The authors demonstrate the importance of AI technologies in improving separate stages of medical care and the circulation of healthcare technologies, and also present various approaches to defining the notion of “artificial intelligence”, that is a crucial element in specifying the object of legal regulation. The article systematizes the list of threats and challenges to human security associated with the use of AI technologies. The development of legal regulation of this sphere at the national (United States of America) and supranational (European Union) levels is analyzed, and also the main directions of development of this field in the Russian Federation are presented.